2018
DOI: 10.3390/app8112296
|View full text |Cite
|
Sign up to set email alerts
|

Further Investigations into the Capacitive Imaging Technique Using a Multi-Electrode Sensor

Abstract: As a novel non-destructive testing technique, capacitive imaging (CI) has been used to detect defects within the insulation layer and metal surface of an insulated metallic structure, that is, pipe or vessel. Due to the non-linearity of the probing field, the defects at different depths in the insulation layer are difficult to compare accurately using the conventional CI sensor with a single pair of electrodes. In addition, the conventional CI sensor cannot provide adequate information to discriminate the defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The structure diagram of the CI sensor is shown in Figure 1(a), where a represents the length of the working electrode, b represents the width of the working electrode, d 1 represents the width of the interelectrode shield electrode and d 2 represents the distance between the working electrode and the interelectrode shield electrode. Previous research results have shown that the capacitance value of the CI sensor is related to the geometric parameters that constitute the sensor, that is, the capacitance value of the theoretical model of the CI sensor is a function of the geometric parameters a, b, d 1 and d 2 (Li et al, 2018a(Li et al, , 2018b. The capacitance value of the CI sensor is composed of two parts: one part is a function related to geometric parameters, and the other part is a function unrelated to geometric parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure diagram of the CI sensor is shown in Figure 1(a), where a represents the length of the working electrode, b represents the width of the working electrode, d 1 represents the width of the interelectrode shield electrode and d 2 represents the distance between the working electrode and the interelectrode shield electrode. Previous research results have shown that the capacitance value of the CI sensor is related to the geometric parameters that constitute the sensor, that is, the capacitance value of the theoretical model of the CI sensor is a function of the geometric parameters a, b, d 1 and d 2 (Li et al, 2018a(Li et al, , 2018b. The capacitance value of the CI sensor is composed of two parts: one part is a function related to geometric parameters, and the other part is a function unrelated to geometric parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Capacitive imaging (CI) technology tests a specimen by using the quasistatic edge electric field generated between coplanar electrodes (Yin et al, 2020a). When defects are present in the specimen, they cause disturbances to the quasistatic edge electric field (Li et al, 2023;Li et al, 2018aLi et al, , 2018bYin et al, 2018). Variations in the capacitance value between coplanar electrodes occur as a result of changes in the quasistatic edge electric field.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that for static electric field, the electric field lines and the equipotential lines are perpendicular to each other [16]. If there is a defect in the quasi-static fringing electric field, both the electric field lines and the equipotential lines will be distorted [17].…”
Section: Simulation Analysis Of the CI Sensor Detecting Surface mentioning
confidence: 99%
“…It has many advantages, such as noncontact, coupling agent free, real-time and intuitive detection results, cost effective and easy to implement [15]. In theory, the CI technique can not only detect surface corrosion defects of the conducting specimen without an insulation layer but also detect surface corrosion defects of the conducting specimen through a relatively thick (up to 100 mm) insulation layer [16]. The principle of CI technique for defect detection is shown in Fig 1. An AC voltage is applied to the driving electrode of a CI sensor, and the sensing electrode of the CI sensor is connected to a measurement circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al studied the capacitive imaging application using a multi-electrode capacitive sensor. The designed sensor was used to detect defects in the insulation layer and the metal surface, and the penetration depth and the signal strength were discussed [19]. Sheldon et al applied the capacitive sensing technique to measure the permittivity of wire insulation materials, and they presented a new equation to calculate the capacitance.…”
Section: Introductionmentioning
confidence: 99%